2013
DOI: 10.4236/fns.2013.48a010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Antioxidative Properties of Phlorotannins Isolated from the Brown Alga <i>Eisenia bicyclis</i>, by the H-ORAC Method

Abstract: The antioxidative properties of phlorotannins isolated from the brown alga Eisenia bicyclis were measured using the H-ORAC (Hydrophilic Oxygen Radical Absorbance Capacity) method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…However, limited information is available on the anti-inflammatory effects of FF among phlorotannins. Particularly, there have been few reports of its biological activities as antioxidant activity [34] and anticancer activity [35]. Therefore, we tried to identify the anti-inflammatory effect of FF in RAW 264.7 cells induced by LPS and we found that FF from edible seaweed E. bicyclis decreased NO and PGE 2 overproduction in LPS-activated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…However, limited information is available on the anti-inflammatory effects of FF among phlorotannins. Particularly, there have been few reports of its biological activities as antioxidant activity [34] and anticancer activity [35]. Therefore, we tried to identify the anti-inflammatory effect of FF in RAW 264.7 cells induced by LPS and we found that FF from edible seaweed E. bicyclis decreased NO and PGE 2 overproduction in LPS-activated RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…The modified Kendrick plot (Shakeri Yekta et al, 2012), or the ratio of Kendrick mass defect to z* (KMD/z*) versus exact mass ( Figure 2B), further underlines the presence of multiple rather extended (≥ 6 members) homologous CH 2 -based series of CHO compounds, with Gaussian-like intensity profiles among homologous series ( Figure 2B) (Gonsior et al, 2016). Phlorotannins are known strong antioxidants and hence can react rapidly with reactive oxygen species (Fujii et al, 2013;Kuda et al, 2006;Le Lann et al, 2016) to likely form new compounds containing additional oxygen (Schmitt-Kopplin et al, 1998;Zhang & Blough, 2016) which might in particular reflect increased hydroxylation on the aromatic rings. To further investigate compositional relationships in Sargassum DOM, nominal transformations were tested originating from CHO formulas that matched known phlorotannins.…”
Section: Composition Of Sargassum Dom Analyzed By Ft-icr Msmentioning
confidence: 89%
“…Phlorotannins correspond to polymerization of phloroglucinol monomer units containing both phenyl and phenoxy units (Li et al 2011). Accumulation of these phloroglucinol-based phenolics contributes to the strong antioxidant activity against free radicalmediated oxidation damage (Kang et al 2012a;Fujii et al 2013). They also show other potential bioactivity such as a bactericidal, antiviral, and anticancer activity and radio protective and antiallergic effects (Li et al 2011;Eom et al 2012;Le Lann et al 2016).…”
Section: Introductionmentioning
confidence: 99%